Advancs geography - Nagle, Garret (New York : Oxford University Press, 2000)
Useful for the A-Level specifications (both AS and A2), this work provides coverage of course requirements. The text is presented in manageable sections. 'Surgeries' explain difficult theories and concepts and 'Seminars' examine issues and controversies. It contains geographical skills and case studies, over 800 illustrations and 1000 questions.
Keywords: Advancs geography